“Succeeding in a speedy life”: Psy knowledge in terms of self-help in Chile and Spain (1940's) - Mariano Ruperthuz Honorato; Universidad de Santiago de Chile/Universidad Diego Portales; Silvia Lévy Lazcano; Investigadora pre-doctoral en el Instituto de Historia del Centro de Ciencias Humanas y Sociales del CSIC de Madrid (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2017)
This article considers the development of self-help therapeutic culture in Chile and Spain in the mid-twentieth century. From a theoretical perspective, the work of Nikolas Rose (1998) and Eva Illouz (2010; 2014) have recognized the prevailing importance that the processes of modernization gave to psy knowledge, understood as a set of disciplines regarding the mind, especially in the reconfiguration of the structure and narrative of the self. Following this theory, two texts -from Chile and Spain respectively- are analysed: ¡Controle su cerebro! (Control your brain!) (1946) and ¿Cómo triunfar? (How to Succeed) (1945). The comparative approach sheds light on how the characteristics of the successful modern subject were presented to the general public: individual, competitive and ambitious. This shows the existence of transnational processes of reception as well as the circulation and implementation of psi knowledge, which will open, in the future, possibilities for further comparative analyses.